Acute cardiac sympathetic disruption and left ventricular wall motion abnormality in takotsubo syndrome. (March 2015) - Y-Hassan, Shams
Abstract Takotsubo syndrome (TS) is characterized by a unique pattern of transient circumferential left ventricular wall motion abnormality (LVWMA). The LVWMA in TS may be localized to the apical, mid-apical, mid-ventricular, mid-basal or basal regions of the left ventricle. Focal and generialized (global) LVWMA have also been reported. In the acute phase of TS, the hyperkinetic valve-like motion of the basal segments and/or the hyperkinetic slingshot-like motion of the apical segments combined with the firm stunned a-, hypokinetic segments result in a conspicuous left ventricular ballooning during systole. The LVWMA in TS follows most probably the local cardiac sympathetic nerve distribution and caused by local cardiac sympathetic disruption and noradrenaline spillover.